The rule of law and armed conflict reconstruction implementation practices: A human right-based analysis of the Rwandan experience - Harry Amankwaah (Cogent Social Sciences)
This study provides a right-based analysis of the rule of law and armed conflict reconstruction implementation practices in Rwanda. It answers the mode of implementation of the ICTR and the Gacaca court system and assessed the consistency of these mechanisms with HRBA principles using a qualitative-content approach. The study revealed the consistency of ICTR operations with the HRBA principle on the rule of law; yet, the Gacaca court system appeared the opposite. Therefore, the need to identify and strengthen specific rule of law mechanisms to prosecute respective human rights and humanitarian law violations to reduce clashes. The study recommends sanctions be applied to all perpetrators of international crimes in accordance with their level of perpetration.